Urban Functional Areas and Their Relations with the Surroundings – an Example of Metropolitan Areas - Korenik, Stanisław (Miejskie obszary funkcjonalne i ich relacje z otoczeniem – przykład obszarów metropolitalnych, 2022)
Modern cities are undergoing intensive changes along with increasing globalisation and developing a knowledge-based economy. As a result of these changes, modern large cities, known as metropolises, are also emerging. With their creation, the surroundings of these cities are also changing. Urban functional areas are being created, often referred to as metropolitan areas. The further surroundings of large cities are also undergoing transformations, however, not always perceived as positive.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 13-22
Keywords: city; metropolis; urban functional areas; region; urban sprawl; miasto; metropolia; miejski obszar funkcjonalny